If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2z + 5 + -5 = z + -5 Reorder the terms: 5 + -5 + 2z = z + -5 Combine like terms: 5 + -5 = 0 0 + 2z = z + -5 2z = z + -5 Reorder the terms: 2z = -5 + z Solving 2z = -5 + z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-1z' to each side of the equation. 2z + -1z = -5 + z + -1z Combine like terms: 2z + -1z = 1z 1z = -5 + z + -1z Combine like terms: z + -1z = 0 1z = -5 + 0 1z = -5 Divide each side by '1'. z = -5 Simplifying z = -5
| 2x+14=49+14x+x^2 | | (7w)-2=60 | | ln(x+5)-ln(5)=ln(20) | | 5t-4=1+25t | | -6d^2+3cd+c-2d= | | (6y^2-7y+2)(4y-3)= | | 45x^2=20 | | y=2/3x^2-3 | | (11v+8)(3v-9)=0 | | 2x+5x=7x | | 9y+3z=34 | | 13x-27=9x-23 | | 13x-27=9x-23 | | 3x-11.2=x | | 0.6x-0.5y=2.4 | | -5x-34=-24 | | 8-9=5t^2 | | 24j-6=14j+7 | | -4x+20=-11 | | x-9y=28 | | 5x^2-10x/13x-26 | | (L-12)2=156 | | (3x+2)(3x^2-10x+7)=0 | | 3c^2-13c-16d^2= | | 12y-15=6y-10 | | L-12*2=156 | | (4-11i)(6+2i)= | | 5x^2-10x/13x=26 | | 2*12-L=156 | | 1/x^2-81 | | 6/2x-1 | | 4x^2+11s-3=0 |